CDK4/6 inhibitors in breast cancer therapy: mechanisms of drug resistance and strategies for treatment - Tong Gao; Ying Sun; Ping Leng; Donghua Liu; Qie Guo; Jing Li (Frontiers in Pharmacology)
Dysregulated cell cycle progression is a well-established hallmark of cancer, driving the development of targeted antitumor therapies that intervene at specific phases of the cell cycle. Among these therapeutic targets, cyclin-dependent kinases 4 and 6 (CDK4/6) have emerged as critical regulators of cell cycle progression, with their aberrant activation being strongly implicated in tumorigenesis and cancer progression. Currently, multiple CDK4/6 inhibitors have received clinical approval for hormone receptor (HR)-positive/human epidermal growth factor receptor 2 (HER2)-negative breast cancer, demonstrating dual therapeutic mechanisms through both cell cycle arrest and enhancement of antitumor immunity. However, clinical implementation faces two major challenges: the inevitable development of acquired resistance during prolonged treatment, and the need for optimized combination strategies with other anticancer agents to achieve synergistic efficacy. This review systematically examines the molecular mechanisms underlying CDK4/6 inhibitor function and characterizes currently approved therapeutic agents. Importantly, it synthesizes recent discoveries regarding resistance mechanisms, including dysregulated cell cycle checkpoints, compensatory signaling pathway activation, and tumor microenvironment adaptations. Furthermore, we critically evaluate emerging combination therapeutic approaches targeting these resistance mechanisms. By integrating mechanistic insights with clinical evidence, this analysis aims to provide actionable strategies for overcoming therapeutic resistance and maximizing the clinical potential of CDK4/6 inhibitors in breast cancer management.